Integrated risk factors for premature acute coronary syndrome: residual cholesterol, RDW, and BMI - Liang, Yansheng; Li, Tingting; Li, Jinlong; Han, Haitao; Cheng, Yanli (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe roles of residual cholesterol (RC), red cell distribution width (RDW), and body mass index (BMI) in premature acute coronary syndrome (ACS) remain underexplored.AimThis study aimed to investigate the significance of RC, RDW, and BMI in the diagnosis of premature ACS.MethodsA retrospective analysis was conducted on 418 ACS patients at Binzhou Medical University Hospital, categorized into early-onset and late-onset groups. Spearman correlation and multivariate logistic regression were used to evaluate associations. Receiver operating characteristic (ROC) curves assessed the diagnostic performance of RC, RDW, BMI, and their combination.ResultsRC and BMI were positively correlated with premature ACS, while RDW was negatively correlated. All three were identified as independent risk factors. A nomogram model highlighted RC as the strongest predictor. The combined model significantly improved diagnostic accuracy, achieving an area under the curve (AUC) of 0.941.ConclusionRC, RDW, and BMI are independently associated with premature ACS, potentially reflecting inflammatory and metabolic mechanisms. Their combined use enhances diagnostic precision and may support early risk stratification in clinical practice.